ANALISIS STRATEGI GURU DALAM PENERAPAN P5 PADA KURIKULUM MERDEKA UNTUK MEMBENTUK KARAKTER PESERTA DIDIK DI SD INPRES 3 TALISE - Muliyani, Ni Made; Anta, I Made Nuhari; Sudarsana, Wayan (STAH Dharma Sentana Sulawesi Tengah, 2024)
This study aims to determine teacher strategies, impacts, obstacles in implementing P5 in the Independent Curriculum to shape the character of students at SD Inpres 3 Talise. Using descriptive methods quantitative approach. The results of the research obtained in the application of P5 were carried out in grades I and IV, teacher strategies in the application of P5 such as: planning the implementation of P5, planting concepts, collaborating with parents, implementing P5 and conducting evaluations. The impact that arises such as increasing critical thinking skills, can improve the school environment, increase motivation, increase creativity and improve social skills of students. And the obstacles are the constraints of learning facilities and the constraints of students who are less active. This research uses questionnaires to determine teacher activities in the application of P5, researchers analyze questionnaires that in grade I teacher activities in the application of P5 are not often carried out while in grade IV teacher activities often apply P5.